Empirical Validation of Complexity and Extensibility Metrics for Software Product Line Architectures - Oliveira Junior, Edson A.; Maldonado, Jose C.; Gimenes, Itana M. S. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2010: Anais do IV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2010)
The software product line (PL) architecture (PLA) is one of the most important PL core assets as it is the abstraction of the products that can be generated, and it represents similarities and variabilities of a PL. Its quality attributes analysis and evaluation can serve as a basis for analyzing the managerial and economical values of a PL. We proposed metrics for PLA complexity and extensibility quality attributes. This paper is concerned with the empirical validation of such metrics. As a result of the experimental work we can conclude that the metrics are relevant indicators of complexity and extensibility of PLA by presenting their correlation analysis.